2010
DOI: 10.1103/physrevlett.105.017202
|View full text |Cite
|
Sign up to set email alerts
|

Direct Phase Probing and Mapping via Spintronic Michelson Interferometry

Abstract: A spintronic approach is introduced to transform classic Michelson interferometry that probes the electromagnetic phase only. This method utilizes a nonlinear four-wave coherent mixing effect. A previously unknown striking relation between spin dynamics and the relative phase of electromagnetic waves is revealed. Spintronic Michelson interferometry allows direct probing of both the spin-resonance phase and the relative phase of electromagnetic waves via microspintronics. Thereby, it breaks new ground for cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 14 publications
1
56
0
Order By: Relevance
“…Indeed, the peculiar line shapes in both cases can be fit by using the combination of symmetric and antisymmetric Lorentzian functions [22]. The fact that such a phase correlation effect is now measured by spin pumping is of particular interest, since it implies that the line shape of spin pumping FMR can be tuned by changing the phase difference between j + (t) and m + (t), as was demonstrated for spin rectification [23]. This may enable microwave coherent control of the pure spin current produced by spin pumping, which was celebrated in semiconductor spintronics by using coherent optical methods [24,25].…”
mentioning
confidence: 88%
“…Indeed, the peculiar line shapes in both cases can be fit by using the combination of symmetric and antisymmetric Lorentzian functions [22]. The fact that such a phase correlation effect is now measured by spin pumping is of particular interest, since it implies that the line shape of spin pumping FMR can be tuned by changing the phase difference between j + (t) and m + (t), as was demonstrated for spin rectification [23]. This may enable microwave coherent control of the pure spin current produced by spin pumping, which was celebrated in semiconductor spintronics by using coherent optical methods [24,25].…”
mentioning
confidence: 88%
“…Such nonlinear terms typically lead to the product of j and m. Spin rectifications induced by such magnetoresistance effects are listed in Table I by the terms labeled V MR . The general feature of V MR is that its amplitude depends on both the relative phase Φ and the spin resonance phase Θ, which leads to a characteristic phase signature of the FMR line shape 37,38 .…”
Section: A Brief Review Of Electrical Detection Of Fmrmentioning
confidence: 99%
“…The line shape analysis for the perpendicular case can be found in Ref. 37. In both cases the form of the susceptibility, χ ∝ D + iL, describes the ferromagnetic resonance line shape where each element of χ is the sum of an antisymmetric and symmetric Lorentz line shape.…”
mentioning
confidence: 99%
“…Other studies have also shown that the relative phases of electromagnetic waves are important to consider in FMR exeriments 33,34 . Hence, the phase lag between the applied MW field and the induced field needs to be considered.…”
Section: B Magnetic Field From a Circular Current Loopmentioning
confidence: 99%